2017
DOI: 10.5194/wes-2-547-2017
|View full text |Cite
|
Sign up to set email alerts
|

Using wind speed from a blade-mounted flow sensor for power and load assessment on modern wind turbines

Abstract: Abstract.In this paper an alternative method to evaluate power performance and loads on wind turbines using a blade-mounted flow sensor is investigated. The hypothesis is that the wind speed measured at the blades has a high correlation with the power and loads such that a power or load assessment can be performed from a few hours or days of measurements.In the present study a blade-mounted five-hole pitot tube is used as the flow sensor as an alternative to the conventional approach, where the reference wind … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Some field measurement campaigns were punctually performed for research purposes using pressure probes around the blades on dedicated blade manufacturing with however only weak potential of these sensors to be used in a day-to-day operation of wind turbines [26]. Some solutions were explored such as tufts or stall flags glued on the blade correlated with positions of the flow separation [25,20] [7]. However, these methods need a mounted camera on the turbine with its associated drawbacks (fragility of the camera, vision at night ...).…”
Section: Introductionmentioning
confidence: 99%
“…Some field measurement campaigns were punctually performed for research purposes using pressure probes around the blades on dedicated blade manufacturing with however only weak potential of these sensors to be used in a day-to-day operation of wind turbines [26]. Some solutions were explored such as tufts or stall flags glued on the blade correlated with positions of the flow separation [25,20] [7]. However, these methods need a mounted camera on the turbine with its associated drawbacks (fragility of the camera, vision at night ...).…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al (2006Shen et al ( , 2009, Guntur and Sørensen (2014) and Rahimi et al (2017) present several methods to calculate the flow near the airfoil that also take 3D effects into account, but the methods require information that cannot be obtained directly from a BMFS. Pedersen et al (2017) describes how to obtain the effective 3D inflow from the relative wind speed and two perpen- From the relative velocity, V rel , the wind speed at the rotor plane, V r , is found by subtracting the velocity of the sensor, V s :…”
Section: Wind Speed From a Bmfsmentioning
confidence: 99%
“…These relative curves can be used to investigate e.g. aerodynamic modifications or detect performance 20 issues (Pedersen et al, 2017).…”
mentioning
confidence: 99%
“…Shen et al (2006Shen et al ( , 2009, Guntur and Sørensen (2014), and Rahimi et al (2018) present several methods to calculate the flow near the airfoil that also take 3-D effects into account, but the methods require information that cannot be obtained directly from a BMFS. Pedersen et al (2017) describes how to obtain the effective 3-D inflow from the relative wind speed and two perpendicular angles measured by a blade-mounted five-hole pitot, including compensation for bound circulation. The compensation method uses a look-up table generated by 2-D computational fluid dynamic (CFD) simulations, thus neglecting 3-D effects and tip and root vortices.…”
Section: Wind Speed From a Bmfsmentioning
confidence: 99%
“…Furthermore, the load distribution along the blade should be taken into account, such that the sensor measures the inflow where the largest loads occur. In Pedersen et al (2017), different radial positions are investigated and 50-67 was found to be optimal.…”
Section: Introductionmentioning
confidence: 99%